2017
DOI: 10.1371/journal.pone.0173418
|View full text |Cite
|
Sign up to set email alerts
|

Persistent fibrosis, hypertrophy and sarcomere disorganisation after endoscopy-guided heart resection in adult Xenopus

Abstract: Models of cardiac repair are needed to understand mechanisms underlying failure to regenerate in human cardiac tissue. Such studies are currently dominated by the use of zebrafish and mice. Remarkably, it is between these two evolutionary separated species that the adult cardiac regenerative capacity is thought to be lost, but causes of this difference remain largely unknown. Amphibians, evolutionary positioned between these two models, are of particular interest to help fill this lack of knowledge. We thus de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
39
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 66 publications
(91 reference statements)
3
39
0
Order By: Relevance
“…It is particularly advantageous for the X. laevis tadpole, then, that ventricular volume in our model returns to control levels within 48 hr of removal from light, which indicates a rapid and robust recovery response. In contrast, hypertrophy observed in adult X. laevis hearts following ventricular amputation remained present up to 11 months after surgery (Marshall et al., ).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…It is particularly advantageous for the X. laevis tadpole, then, that ventricular volume in our model returns to control levels within 48 hr of removal from light, which indicates a rapid and robust recovery response. In contrast, hypertrophy observed in adult X. laevis hearts following ventricular amputation remained present up to 11 months after surgery (Marshall et al., ).…”
Section: Discussionmentioning
confidence: 98%
“…A closer look at the cellular structure of the cardiomyocytes during this stage would be very informative as to the extent of the dedifferentiation process and to what degree it is required for recovering from the effects of oxidative stress. Interestingly, no change in markers of proliferation was observed in adult X. laevis following ventricular amputation, which may indicate that this repair ability, like limb regeneration, is lost between tadpole stages and adulthood, and perhaps requires extant expression of cardiac progenitor genes (Marshall et al., ). The presence of proliferation in similarly amputated X. tropicalis frogs at the young adult stage may further narrow down the time at which cardiomyocyte proliferation becomes no longer possible, if the difference is one of age and not species (Liao et al., , ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Proliferation of cardiomyocytes is a known driver of cardiac regeneration in non-mammalian species and neonatal mammals (Cano-Martínez et al, 2010; Flink, 2002; Gonzalez-Rosa et al, 2011; Lai et al, 2017; Liao et al, 2017; Porrello et al, 2011; Sallin et al, 2015; Schnabel et al, 2011; Stockdale et al, 2018; Vargas-González et al, 2005; Yu et al, 2018); further, a regenerative phenotype has not yet been reported in the absence of cardiomyocyte proliferation (Ito et al, 2014; Lin and Pu, 2014; Marshall et al, 2017). However, the recent finding of widespread cardiomyocyte proliferation in non-regenerative Pachón Astyanax mexicanus suggests that this behavior is not the sole factor that dictates a regenerative response (Stockdale et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the non-regenerative Pachón Astyanax mexicanus exhibits a similar peak in non-myocyte proliferation at this timepoint, but only in remote regions of the heart rather than the injured zone (Stockdale et al, 2018). Non-regenerative Xenopus laevis do not exhibit increased cell proliferation at all (Marshall et al, 2017). Localized proliferation of non-myocytes has thus far only been described in zebrafish and axolotl; however, this occurs at much earlier stages, peaking 1 week post-injury (Chablais et al, 2011; Godwin et al, 2017; Gonzalez-Rosa et al, 2011; Sánchez-Iranzo et al, 2018; Schnabel et al, 2011; Xu et al, 2018; Yu et al, 2018).…”
Section: Discussionmentioning
confidence: 99%